Novas determinações do capital na saúde brasileira: a Empresa Brasileira de Serviços Hospitalares em questão - Cardial, Andréa Mattos Dantas do Nascimento (2013)
This dissertation aims at analyzing the creation and implementation of the Brazilian Hospital Services (Ebserh) as part of the process contrarreforma of the Brazilian state of health. As a result, its specific objectives were to discuss the role of the state and its relation to the proposals of contrarreforma in health, to recover the trajectory and characteristics of PL on the State Foundations of Private Law with emphasis on management of HU´s, check purposes the Ebserh about the formative nature of HU´s; identify the (s) model (s) proposed management (s) within the Ebserh, focusing on human resources, identify the proposed management of financial resources of Ebserh for maintenance of HU´s. Methodologically data were collected by means of desk research and literature. Among the main results, we find that the Ebserh corresponds to a reissue project of private foundations who was unsuccessful with regard to University Hospitals, its adoption has served as a form of appropriation of public fund health by capital; tends to expand the forms of precarious work and mischaracterize the formative role of these units as teaching hospitals.